2020
DOI: 10.1111/joor.13099
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical tongue cleaning is a worthwhile procedure to improve the taste sensation

Abstract: Background: There are still only a few therapeutic strategies to improve taste sensation, which is part of oral health and quality of life. Objective: Therefore, here we aimed to investigate gustatory functions of healthy subjects performing mechanical tongue cleaning (MTC), an easy-to-perform oral hygiene procedure, to demonstrate taste changes and to describe possible negative side effects. Methods: Prior to and 14 days following MTC with an Orabrush ® , the following tests were conducted in 65 healthy parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
3
0
4
Order By: Relevance
“…Routine mechanical tongue cleaning improves gustatory function. 14 Seerangaiyan et al study 7 also reinforced that tongue brushing can increase salty taste sensitivity. However, another study by Solemdal et al 15 found there is no correlation between taste sensitivity and coated tongue.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Routine mechanical tongue cleaning improves gustatory function. 14 Seerangaiyan et al study 7 also reinforced that tongue brushing can increase salty taste sensitivity. However, another study by Solemdal et al 15 found there is no correlation between taste sensitivity and coated tongue.…”
Section: Discussionmentioning
confidence: 90%
“…They also suggested that tongue brushing, which was accompanied by mechanical stimulation of the tongue surface might increase blood flow within tongue papillae to increase taste sensitivity. 14 Daily tongue cleaning (at least once a day) would have better impact on reducing tongue coating and improving taste sensitivity level than weekly (once a week, or not every day). 18 In conclusion, good oral health is needed to maintain gustatory function.…”
Section: Discussionmentioning
confidence: 99%
“…Предполагается, что механическое удаление налета со спинки языка освобождает доступ пищи через вкусовые поры к вкусовым рецепторам [24] и, следовательно, позволяет поддерживать/восстановить базовую вкусовую чувствительность, что считается важным с гедонистической точки зрения и определяющим формирование аппетита и чувства насыщения, а также объем потребления соли и сахара, риск переедания и недоедания, то есть уровень здоровья и качество жизни человека [25]. Наиболее активно эта тема обсуждается в гериатрии [26][27][28] (при нормальном старении, в частности, ухудшаются параметры саливации, сокращается количество грибовидных сосочков и деградируют вкусовые луковицы, уплотняются стенки сосудов передних третей языка [25,29]): механическая чистка языка, в процессе которой не только снимают ЛН, но одновременно стимулируют тройничный нерв [24], кровоток [29] и саливацию [25], представляется чуть ли не единственной реальной стратегией для снижения вкусовых порогов и повыше ния надпорогового восприятия интенсивности вкуса у пожилых и старых людей [27,29].…”
Section: чистка языка и вкусовая чувствительностьunclassified
“…Результаты десятка исследований подтверждают, что субъективная оценка чувствительности к основным вкусам, а также результаты объективных тестов вкусовой «Стоматология Эстетика Инновации», 2023, том 7, № 2 Лекции и обзоры Lectures and Reviews функции повышаются после чистки языка, что заметно даже после однократной процедуры скрапинга [24] и дает устойчивые результаты спустя 10-14 дней регулярной чистки языка [26,29]. Отмечено, что описанный эффект больше выражен у людей старшего возраста [29] (порог для соленого восстанавливается до показателей молодых участников исследования) и ярче проявляется в отношении кислого, горького и соленого вкусов [25].…”
Section: чистка языка и вкусовая чувствительностьunclassified
“…Removal of tongue coating using mechanical tongue cleaning improves gustatory functions regardless of smoking habits. 50,51 A study targeted at nurses demonstrated that tongue cleaning with tongue brushing improved taste sensation; in contrast, using mouth rinse did not change its threshold, 52 suggesting that mechanical stimulation of the tongue's dorsum is critical to improving the sensation of taste. A study on gustatory function in older adults revealed that removing the tongue coating twice a day improves their perception of taste.…”
Section: Tong Ue Cle Aning For Removing Tong Ue Coatingmentioning
confidence: 99%